The correlation of perception in biology lessons with the learning outcomes of students cross-interests on ecosystem concepts - Dea Noor Afifah; Rinaldi Rizal Putra (Universitas Ahmad Dahlan, 2021)
Students' perceptions of a subject or concept will have an impact on the perspective of students in facing the learning process. Perceptions built by students towards a lesson or concept must always be positive so that the learning outcomes achieved can be maximized. This study aims to determine the relationship between students' perceptions in the Biology subject with the learning outcomes of students across Biology interests at SMA Negeri 6 Kota Tasikmalaya. This research is a correlational study that links perceptions with student learning outcomes on the concept of ecosystems. The population of all class X IPS was five classes, and a sample of 1 class amounted to 34 students, namely in class X IPS 5 as participants with the sampling technique using purposive sampling. The class is sampled based on the consideration of the lowest average score compared to other classes. The research instruments used included questionnaires from other studies that were adapted and adapted to the ecosystem concept and multiple-choice tests to measure student learning outcomes. The student perception questionnaire consists of 28 statements. Each item has an alternative answer consisting of 4 choices, namely strongly agree (SS), agree (S), disagree (TS), strongly disagree (STS). While the learning outcome test was measured using multiple-choice questions, the ecosystem material consisted of 46 questions. The data analysis technique used was the bivariate correlation regression test. Prior to data analysis, the normality test and linearity test were performed first as a prerequisite test for analysis. The results showed that there was a relationship between perceptions and student learning outcomes on the ecosystem concept of 38.9% with a strong category.